Phase 3 trial of human islet‐after‐kidney transplantation in type 1 diabetes. Issue 4 (9th August 2020) - Markmann, James F.; Rickels, Michael R.; Eggerman, Thomas L.; Bridges, Nancy D.; Lafontant, David E.; Qidwai, Julie; Foster, Eric; Clarke, William R.; Kamoun, Malek; Alejandro, Rodolfo; Bellin, Melena D.; Chaloner, Kathryn; et al.
Abstract : Allogeneic islet transplant offers a minimally invasive option for β cell replacement in the treatment of type 1 diabetes (T1D). The CIT consortium trial of purified human pancreatic islets (PHPI) in patients with T1D after kidney transplant (CIT06), a National Institutes of Health–sponsored phase 3, prospective, open‐label, single‐arm pivotal trial of PHPI, was conducted in 24 patients with impaired awareness of hypoglycemia while receiving intensive insulin therapy. PHPI were manufactured using standardized processes. PHPI transplantation was effective with 62.5% of patients achieving the primary endpoint of freedom from severe hypoglycemic events and HbA1c  ≤ 6.5% or reduced by ≥ 1 percentage point at 1 year posttransplant. Median HbA1c declined from 8.1% before to 6.0% at 1 year and 6.3% at 2 and 3 years following transplant ( P  < .001 for all vs baseline), with related improvements in hypoglycemia awareness and glucose variability. The improved metabolic control was associated with better health‐related and diabetes‐related quality of life. The procedure was safe and kidney allograft function remained stable after 3 years. These results add to evidence establishing allogeneic islet transplant as a safe and effective treatment for patients with T1D and unstable glucose control despite intensive insulin treatment, supporting the indication for PHPI in the post–renal transplant setting. Abstract : The NIH‐sponsored Clinical Islet Transplant Consortium phase III trial of isolated pancreatic islet transplantation in patients after kidney transplant shows that the procedure is safe and effective at normalizing A1c, preventing severe hypoglycemic events, and improving patient quality of life. An editorial from Fridell and Stratta is on page 1363 .